The Hanse in medieval and early modern Europe - Wubs-Mrozewicz, Justyna 1976-; Jenks, Stuart (Leiden Brill, 2013)
The Hanse in Medieval and Early Modern Europe discusses new research on this unique organization of towns and traders, and places the findings in the broader context of European economic, legal and social history.
CSSP-7982 donated by Brill Publsihers through SPi Global Foundation, Inc.
Keywords: Hanseatic League -- History; Commerce -- History -- Medieval, 500-1500.; Commerce -- History -- 16th century; Hansa towns -- History; Europe -- Commerce -- History